IFIH1 Contributes to M1 Macrophage Polarization in ARDS - Zhang, Shi; Chu, Cuilin; Wu, Zongsheng; Liu, Feng; Xie, Jianfeng; Yang, Yi; Qiu, Haibo (Frontiers in Immunology, 2021)
Accumulated evidence has demonstrated that the macrophage phenotypic switch from M0 to M1 is crucial in the initiation of the inflammatory process of acute respiratory distress syndrome (ARDS). Better insight into the molecular control of M1 macrophages in ARDS may identify potential therapeutic targets. In the current study, 36 candidate genes associated with the severity of ARDS and simultaneously involved in M1-polarized macrophages were first screened through a weighted network algorithm on all gene expression profiles from the 26 ARDS patients and empirical Bayes analysis on the gene expression profiles of macrophages. STAT1, IFIH1, GBP1, IFIT3 and IRF1 were subsequently identified as hub genes according to connectivity degree analysis and multiple external validations. Among these candidate genes, IFIH1 had the strongest connection with ARDS though the RobustRankAggreg algorithm. It was selected as a crucial gene for further investigation. For in vitro validation, the RAW264.7 cell line and BMDMs were transfected with shIFIH1 lentivirus and plasmid expression vectors of IFIH1. Cellular experimental studies further confirmed that IFIH1 was a novel regulator for promoting M1 macrophage polarization. Moreover, gene set enrichment analysis (GSEA) and in vitro validations indicated that IFIH1 regulated M1 polarization by activating IRF3. In addition, previous studies demonstrated that activation of IFIH1-IRF3 was stimulated by viral RNAs or RNA mimics. Surprisingly, the current study found that LPS could also induce IFIH1-IRF3 activation via a MyD88-dependent mechanism. We also found that only IFIH1 expression without LPS or RNA mimic stimulation could not affect IRF3 activation and M1 macrophage polarization. These findings were validated on two types of macrophages, RAW264.7 cells and BMDMs, which expanded the knowledge on the inflammatory roles of IFIH1 and IRF3, suggesting IFIH1 as a potential target for ARDS treatment.